Spontaneous subperiosteal orbital haemorrhage (SSOH): an unusual complication of acute coronary syndrome treatment - Sivaratnam, Dhashani; W Md Kasim, Wan Mariny; Kanasan, Kirbashini; Ming, Teck Yap; Siew, Mooi Ching; Devaraj, Navin Kumar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Acute coronary syndrome is a medical emergency with a high mortality and morbidity. Reperfusion therapy is widely used in its management. Ocular complications following reperfusion therapy is rare. A 51-year-old man treated with streptokinase, antithrombotic and dual antiplatelet therapy, developed mild proptosis following treatment. After four days, there was sudden worsening of the proptosis associated with orbital compartmental syndrome (OCS). The CT scan of the orbit showed a large spontaneous subperiosteal orbital hemorrhage (SSOH) occupying half of the left orbit. Despite performing an urgent lateral canthotomy and inferior cantholysis, the patient developed irreversible vision loss due to compressive optic neuropathy. While a few cases of mild SSOH have been reported in the medical literature, this is the first documented case of secondary bleed in SSOH. Early recognition and intervention by the treating physician, is crucial in preventing blindness.